T Cells Control Chemokine Secretion by Keratinocytes - Rauschenberger, Tabea; Schmitt, Viola; Azeem, Muhammad; Klein-Hessling, Stefan; Murti, Krisna; Grän, Franziska; Goebeler, Matthias; Kerstan, Andreas; Klein, Matthias; Bopp, Tobias; Serfling, Edgar; Muhammad, Khalid (Frontiers in Immunology, 2019)
The massive infiltration of lymphocytes into the skin is a hallmark of numerous human skin disorders. By co-culturing murine keratinocytes with splenic T cells we demonstrate here that T cells affect and control the synthesis and secretion of chemokines by keratinocytes. While pre-activated CD8+T cells induce the synthesis of CXCL9 and CXCL10 in keratinocytes and keep in check the synthesis of CXCL1, CXCL5 and CCL20, keratinocytes dampen the synthesis of CCL3 and CCL4 in pre-activated CD8+T cells. One key molecule is IFN- that is synthesized by CD8+T cells under the control of NFATc1 and NFATc2. CD8+T cells deficient for both NFAT factors are unable to induce CXCL9 and CXCL10 expression. In addition, CD8+T cells induced numerous type I IFN-inducible ‘defense genes’ in keratinocytes including the PD1 and CD40 ligands, TNF- and caspase-1. The enhanced expression of type I IFN-inducible genes resembles the gene expression pattern at the dermal/epidermal interface in lichen planus, an inflammatory T lymphocyte-driven skin disease, in which we detected the expression of CXCL10 in keratinocytes in close vicinity to the infiltration front of T cells. These data reflect the multi-faceted interplay of lymphocytes with keratinocytes at the molecular level.